The conditional inclusion of Muslims in medicine: intersectional experiences of Muslim medical students at the University of Toronto’s Faculty of Medicine from 1887-1964 - Jahangeer, Roshan Arah; Whitehead, Cynthia; Najeeb, Umberin (Canadian Medical Education Journal, 2024)
Background: Archival research has unearthed processes of exclusion impacting the experiences of Black, female, and Jewish communities at Canadian medical schools. However, the history of Muslim medical students is little known. Our research is the first known study to examine when Muslim medical students with varying identities were first admitted to the University of Toronto’s (UofT) Faculty of Medicine (FoM) and their experiences. Knowing this history can contribute to ongoing equity, diversity, and inclusion efforts in medical school admissions and curriculum development. Methods: This is an exploratory case study with no clear, single set of expected outcomes. We consulted the UofT’s Archive & Record Management Services and looked for students who self-identified as Muslim in primary documents from the FoM between 1887-1964, including admissions applications, correspondences from the Dean’s Office, photographs, and yearbooks. We analysed the archival data for emerging themes. Results: We found six medical school applicants who self-identified as Muslim (n = 6) and were admitted between 1945 and 1961 and graduated between 1948 and 1966. We also found four (n = 4) postgraduates from one South Asian country who may have been Muslim, and who were granted fellowships from the Canadian government. Conclusions: Self-identified Muslim students were first admitted to the UofT’s FoM in 1945 and continued to be admitted infrequently until 1964. These early students’ experiences included financial hardships despite having privileged backgrounds; discrimination due to being foreign; and conditional inclusion while in medical school. We discuss the study’s continuing contemporary relevance, limitations, and directions for future research.